Information- measuring system for multidimentional vibration diagnostic - Яворський, І. М.; Юзефович, Р. М.; Кравець, І. Б.; Мацько, І. Й.; Стецько, І. Г. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2013)
The new approach for multidimensional vibration diagnostic based on methods of nonstationary random processes theory and correlation tensor analysis for complex rotating machines diagnostic is proposed. The verification of developed methods on industrial objects of Ukraine and vibration test bench is shown. The portative vibration diagnostic system which utilizes the developed methods is described.